Stop, think, participate! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A co-ordinator of the Kenya Forests Working Group describes how it has been working with local forest management committees, to set up forest use agreements and educate communities in improved forest management methods.